Effects of osmotic and cold shock on adherent human mesenchymal stem cells during cryopreservation. - Xu, X; Liu, Y; Cui, Z; Wei, Y; Zhang, L (2012)
Cryopreservation is one of the most practical methods for the long-term storage of cell-matrix systems to ensure off-shelf availability in tissue engineering, stem cell therapy and drug testing. The aim of this study is to investigate the effects of osmotic and cold shock caused by the procedures of cryoprotectant agent addition/removal and freezing during cryopreservation on cell viability, intracellular properties, such as filamentous actin distribution, mitochondria localization and intracellular pH, and further recovery of adherent human mesenchymal stem cells. Our results shows a significant decrease in cell viability around 30% after cryopreservation at the cooling rates of 1, 5 and 10°C/min in comparison to the adherent cells and the cells in suspension, implicating that the adherent cells are more vulnerable than the suspension cells. The osmotic shock and cold shock induced by freezing lead to dramatic changes in the intracellular properties. The cooling rate of 10°C/min results in acidification of intracellular pH, distortion and accumulation of filamentous actin, and aggregation of mitochondria. Our findings also suggest that the cooling rate of 1°C/min helps to maintain cell morphology and attachment, integrity and uniformity of filamentous actin, and leads to better cell recovery after cryopreservation.